(untitled) (International Journal of Engineering and Computer Science, 2013)
In this paper we have some modification in Playfair Cipher Substitution Technique. We have proposed a method to enhance the Playfair cipher for more secure and efficient cryptography. We use 8X8 Playfair cipher and have made use of a Simple Columnar Transposition Technique with Multiple Rounds in 8X8 Playfair Cipher Substitution Technique and arranged a special symbol by overall Character Frequency Analysis (CFA) .